PENYELENGGARAAN TATA PEMERINTAHAN YANG BAIK DI LINGKUNGAN PEMERINTAH KECAMATAN DI KOTA SAMARINDA - . Djumadi; Pracahaya Pradana Putra; Yayuk Rifqi Masruroh; . Syamsinar; Rido Cahyawan; Abdul Kadir Jailani (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
The principles of good governance are characteristics that must be met in the implementation of good governance, which relates to the control of a government in order to achieve the results desired by stakeholders. Hence the research on the implementation of good governance, which is reviewed through the application of a number of principles of good governance in the regional government in the regional government becomes a means to assess the fulfillment of public needs by the government. This study compares the implementation of good governance in several sub-district governments in the city of Samarinda, which shows that the application of the principles of accountability, transparency and justice/equality still needs improvement so that it can be carried out better for meeting community expectations. Keywords: good governance, accountability, transparency, responsiveness.